The population of Long jawed spider (Tetragnatha maxillosa) during growing phase of paddy at kawasan Sawah Tengah Padang, Merlimau Melaka / Siti Nor Syahira Basri - Basri, Siti Nor Syahira (Faculty of Plantation and Agrotechnology, 2019)
In agricultural practice, the beneficial insect or natural enemies is one of important to control the insect pest in paddy in Malaysia. In order to get the high yields of paddy in whole year, the study were conducted to determine the population dynamic of natural enemies in paddy and conducted by weekly and also to determine the diversity of alternate host plant and its relation to natural enemies in paddy farming surrounding area. The population of long-jawed spider Tetragnatha maxillosa was collected by weekly in ten weeks by using the yellow sticky traps. The result showed that there is no significant in mean of Tetragnatha maxillosa for whole sampling period since (p=0.846) more than 5% (p>0.05). It also showed the interaction of alternate host plant such as Ludwigia perennis, Echinocloa colona, Panicum maximum, Fimbristylis globusa, Setarid palmifolia, Euphorbia heterophylla, Spermacoce verticillata and Chloris barbata and Tetragnatha maxillosa low and no significant. So, it can conclude that the populations of Tetragnatha maxillosa were not influenced by presence of host plant surrounding paddy fields as their habitat.